PELATIHAN PENYUSUNAN KARYA TULIS ILMIAH UNTUK GURU-GURU MATA PELAJARAN IPA SMA - suyatno sutoyo; Budi Jatmiko; Endang Susantini; Wahono Widodo; Utiya Azizah; Sophia Allamin (Universitas Djuanda Bogor, 2021)
The community service activity is intended to improve the ability of high school science teachers in Magetan districts to compile scientific papers. The number of teachers involved in this activity was 25 people consisting of chemistry, physics and biology teachers. The activity was conducted at SMAN 1 Magetan, on Saturday, July 27, 2019. The approach used in the community service activity was a participatory approach, while the method applied in mentoring was the adult learning method (andragogy). The community service activity was begun with the presentation of training materials by the team, followed by mentoring to make scientific papers, and end with reflection and questionnaires. The results of the activity showed that the trainees had the knowledge and skills in developing scientific papers. The trainees showed a positive response to the training activities carried out by the PKM Team. The ability of trainees in compiling scientific papers were quite good with an average score 3.1 (scale 4).